Capital Flight of Foreign Direct Investment From Indonesia to Vietnam: Geopolitical Tensions and Policy Divergence in Southeast Asia - Salma Fatimah; Bambang W. Nugroho (International Journal Labs, 2025)
This research examines the capital flight of foreign direct investment (FDI) from Indonesia to Vietnam against the backdrop of escalating U.S.-China tensions and restructuring global supply chains. Employing a qualitative-comparative methodology, we analyze secondary data from UNCTAD, ASEAN Investment Reports, and World Bank indicators, complemented by policy documents from both nations. Through comparative content analysis and case studies of firms such as Samsung and Foxconn, we identify key drivers of FDI diversion, including trade policy frameworks, geopolitical positioning, and industrial ecosystems. Our findings reveal that Vietnam’s strategic trade diplomacy exemplified by its participation in the CPTPP and EVFTA has bolstered its geopolitical neutrality and FDI attractiveness. In contrast, Indonesia’s resource nationalism, particularly its nickel export ban and rigid downstreaming policies, has discouraged high-tech investments, redirecting capital toward Vietnam’s integrated supply chains and special economic zones (SEZs). For instance, Samsung’s 18 billion investment in Vietnam highlights the shift of labor-intensive manufacturing away from Indonesia. This research contributes to the international political economy literature by demonstrating how policy competition and geopolitical hedging influence FDI redistribution in Southeast Asia. It underscores the trade-offs between resource sovereignty and FDI retention, offering policymakers insights into balancing industrial ambitions with global investor expectations. Future studies should explore firm-level decision-making dynamics and illicit financial flows, such as trade misinvoicing, to further elucidate capital flight mechanisms.